ROSELLA (coffee table) / Tasnim Abd Rahman - Abd Rahman, Tasnim (Universiti Teknologi MARA, Kedah, 2018)
ROSSELLA is on urban concept coffee table. Given the name ROSSELLA, this coffee table influence by the excotic Roselle plant. The originality of ROSSELLA suits the environment ofmodern livingrooms. Despite its modern look. the structure of steel gives a industrial concept vibe to ROSSELLA. Modern and urban concept is a very unique combination. ROSSELLA is biophilic furniture that suitable to put at livingrooms.